KEMAMPUAN MANAJEMEN NYERI ANTARA YANG DIBERIKAN PENKES TEHNIK NAFAS DALAM DAN YANG TIDAK DIBERIKAN PENKES TEHNIK NAFAS DALAM PADA PASIEN POST OF FRAKTUR RSUD H.SAHUDIN KUTACANE TAHUN 2021 - Nurhasanah Sym; Nurjannah Nurjannah (Universitas Prima Indonesia, 2021)
Pain complaints in patients post-surgery fractures are the most common complaints we find/get when we are doing our duty as part of a health team. Complaints of pain are related to physiological, psychological, social, cognitive, emotional and behavioral responses, so that in the treatment of pain in postoperative patients not only use drugs but must be collaborated with the provision of pain health education. This study is Quasi Experimentation with cross sectional study design. With the aim to find out and analyze the comparison of pain management capabilities provided by pain management health education with those not given in H.Sahudin Kutacane Hospital in 2021. The sample number in the study was 46. Researchers use observation sheets as guidelines for collecting needed data. Analyze the data using the chi-Square test with a result of P = 0.000 (P< 0.05). The results of this study showed a difference in ability between before and after being given health education with a value of P = 0.000. This shows that there is a difference in pain management ability between those given health education and those not given in postoperative surgery at H.Sahudin Kutacane Hospital In 2021. Based on the results of research conducted researchers are expected to nurses, especially post-operative fracture inpatient room nurses to provide health eduction to postoperative patients.